Residents' acceptance towards car-free street experiments: Focus on perceived quality of life and neighborhood attachment. (June 2022) - Marcheschi, Elizabeth; Vogel, Nina; Larsson, Anders; Perander, Sonja; Koglin, Till
Highlights: Car-free street urban experiments. Residents' perception acceptance and usability of car-free streets interventions. Neighbourhood attachment and quality of life influences on car-free streets acceptance. Abstract: While the twentieth century was dominated by private car usage, shifts towards more sustainable urban mobility, to mitigate environmental damage and increase health benefits, are now taking place. In Scandinavia, several car-free street experiments take form, that span from permanent car-free inner-city plans (i.e. Oslo) to temporary interventions (i.e. pop-up plaza and parklets) to shift the use of urban settings and infrastructures from motorised traffic towards spaces for people and social interactions. Specifically, in Sweden, transitory car-free street experiments (i.e. summer streets) are developed with the purpose of creating novel mobility patterns and uses of public spaces that enhance social inclusion and quality of life. Despite Swedish municipalities' monitoring of these interventions, very little is known about which physical parameters (i.e. environmental qualities) and psychosocial processes (i.e. emotional relation with places) affect people's acceptance and place usability during car-free initiatives. Following the guidelines proposed by the European Commission, this paper focuses on residents' perception of car-free street experiments. The aim is to identify how acceptance and usability of car-free street experiments might vary depending on the perceived qualities of the physical urban settings and on interceding psychosocial processes such as, neighborhood attachment and perceived quality of life. An interdisciplinary methodology of investigation merging knowledge from the field of environmental psychology, landscape architecture, urban transport and planning was applied on four case studies in Sweden. Results suggest that psychosocial processes of place attachment and quality of life are relevant in order to understand the level of acceptance towards car-free streets implementations.